PERBANDINGAN SISTEM PARLEMEN BIKAMERAL DI INDONESIA DAN FILIPINA : Comparison Of The Bicameral Parliament System In Indonesia And The Philippines - Ibnu Kuncoro; Ninuk Wijiningsih (Reformasi Hukum Trisakti, 2024)
The bicameral parliamentary is a system of division of chambers in parliaments. The chambers of Parliament are divided into two chambers, consisting of the upper house and the lower house. In Indonesian parliament, there are still differences of opinion among experts on the application of which chamber system. Some experts argue that Indonesia implements soft bicameralism, and some argue that Indonesia also applies tirkameral. Based on this, comparison of the bicameral systems in Indonesia and the Philippines was carried out. The problem of this research is: 1) Are the differences and similarities of the bikameral system in the legislative bodies of Indonesia and Filipina?, 2) Are the advantages and disadvantages of the bicameral scheme applied by Indonesia and the Philippines? This research is typical normative juris, which is descriptive, with primary sources of secondary data, which are analyzed qualitatively with the method of deductive inference. The result and conclusion of the study is that there is a fundamental similarity in the bicameral parliamentary system in Indonesia and the Philippines: all legislative bodies are elected by general election, as well as obtaining the common duties of the legislative body, and there are differences in the balance of powers between the chambers.